ANALISIS KEPUASAN ORANG TUA TERHADAP LAYANAN PENDIDIKAN DI SMP IT LUQMAN AL HAKIM SLAWI TAHUN PELAJARAN 2025/2026 - Anita Triyastuti; Habibi, Beni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of parental satisfaction with educational services provided by SMP IT Luqman Al Hakim Slawi during the 2025/2026 academic year. The research employed a descriptive quantitative approach using a survey method. The respondents consisted of 160 parents who completed an online satisfaction questionnaire. Data were analyzed using descriptive statistical techniques through percentage and mean score calculations. The results indicated that parents generally expressed high satisfaction with the services provided by the school. Communication services between homeroom teachers and parents achieved the highest satisfaction level (87.19%), followed by learning quality (85.00%), school programs (83.59%), school services (81.56%), and student competencies (80.94%). Tahfidz learning outcomes obtained a satisfaction score of 78.59%, Tahsin learning outcomes reached 78.75%, and catering services scored 79.22%. Overall parental satisfaction reached 81.85%, categorized as very satisfied. The findings indicate that communication quality, learning implementation, and school responsiveness are the main factors influencing parental satisfaction. Therefore, schools need to maintain service excellence while strengthening character education, digital literacy supervision, and Qur’anic learning support programs.